Bargaining for Punishment in Corruption Crime: Toward Justice from a Victimology Perspective - Angga Aldilla Gussman; Hafrida Hafrida; Usman Usman; Sahuri Lasmadi; Elly Sudarti; Sri Rahayu (PT. Anagata Sembagi Education, 2024)
Corruption is an extraordinary crime that causes significant losses to the state, both materially and immaterially, which has a broad impact on the economic, social and political stability of a country. As the main victim in corruption crimes, the state bears the burden of recovering the losses incurred. The concept of bargaining for punishment offers an alternative approach in corruption law enforcement by allowing the perpetrator to reduce the sentence through the return of state losses. This research aims to analyze the application of the concept of bargaining for punishment in the context of Indonesian criminal law, especially in realizing justice and benefits for the state as a victim. The method used is Normative Juridical legal research, this research discusses the relevance of bargaining for punishment in bridging the interests of the state for the recovery of losses with the principles of criminal justice. The results show that the application of this concept can accelerate the case settlement process, reduce the burden on the justice system, and maximize the return of lost state assets. However, the application of bargaining for punishment must be closely monitored so as not to harm the principle of justice, especially in dealing with perpetrators with a significant level of guilt. Bargaining for punishment has the potential to become a strategic mechanism in eradicating corruption in Indonesia, provided that it is applied proportionally by considering aspects of justice, expediency, and legal certainty. This research recommends strengthening regulations and guidelines for the implementation of bargaining for punishment to ensure optimal recovery for the state as victims of corruption crimes